Association of Leptin and Ghrelin Serum Levels with Anosmia and Ageusia in Iraqi COVID-19 Infected Patients - Sameerah Jasim Shanyoor, Zahraa Mohammed Ali Naji (Pakistan Journal of Medical & Health Sciences, 2022)
Early indications of COVID-19 infection include anosmia (inability to smell) and ageusia (incapability to taste), which were recorded in up to 85–90% of patients. This investigation was aimed at determining the association of leptin and ghrelin serum levels with anosmia and ageusia in Iraqi COVID-19 infected patients. Three categories of participants were formed in this case-control study: thirty patients infected by COVID-19 at an active state with anosmia and ageusia (group 1), thirty patients infected by COVID-19 without anosmia and ageusia (group 2), and thirty healthy subjects as controls (group 3). The mean serum levels of leptin was significantly higher in group 1, as compared to group 2 and group 3where p-value was (p<0.0001), while the mean serum levels of ghrelin was significantly lower in group 1, as compared to group 2 and group 3wherep-value was (p<0.0001). Blood was obtained from the three groups and the amounts of total leptin and ghrelin in the blood were evaluated. The results showed that the average serum level of leptin was significantly (p < 0.0001) higher in groups 1 and 2 compared to group 3, while the mean serum level of ghrelin was significantly (p < 0.0001) reduced in groups 1 and 2, compared to group 3. It was observed that the occurrence of these changes at the start of the disease is significantly higher, and it is therefore recommended that assessments of smell and taste dysfunction be used as indicators of infection with COVID-19.